2020
DOI: 10.1101/2020.12.07.414730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative profiling of N-respirasomes predicts aberrant mitochondrial bioenergetics at single-cell resolution

Abstract: Mitochondria sustain the energy demand of the cell. The composition and functional state of the mitochondrial oxidative phosphorylation system are informative indicators of organelle homeostasis and bioenergetic capacity. Here we describe a highly sensitive and reproducible method for single-cell visualization and quantification of mitochondrial respiratory supercomplexes as a novel means of measuring mitochondrial respiratory chain integrity. We apply a proximity ligation assay (PLA) and perform comparative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For co-localization indices, Pearson's and Mander's coefficients were determined using the co-localization analysis plugin JACoP. PLA-dots were semi-automatically quantified as previously described [ 32 ].…”
Section: Aterials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For co-localization indices, Pearson's and Mander's coefficients were determined using the co-localization analysis plugin JACoP. PLA-dots were semi-automatically quantified as previously described [ 32 ].…”
Section: Aterials and Methodsmentioning
confidence: 99%
“…PLA experiments were performed using Duolink® PLA fluorescence reagents (Sigma) according to the manufacturer's instructions and as previously described [ 32 ]. Briefly, cells and tissue samples were first permeabilized with 0.25% Triton X-100 in PBS, and then treated with Blocking solution for 1 h at 37 °C.…”
Section: Aterials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it was shown that CHCHD4 can bind the mitochondrial Ca 2+ uptake protein 1 (MICU1) and stimulate the formation of an intermolecular disulfide bond between MICU1 and its paralog MICU2, resulting in aberrant regulation of mitochondrial Ca 2+ uptake. 69 In Drosophila and in mammalian cells, AIF deficiency may compromise IMS import and cristae junction localization of CHCHD3/MI19, 56 , 71 thus disrupting mitochondrial contact site and crista organizing system (MICOS) complex to an extent that phenotypically resembles CHCHD4/MIA40 loss in HeLa cells and yeast. 72 , 73 , 74 The impact of AIF deficiency on MICOS complex stability is not limited to one single subunit, but extends to others, such as coiled-coil-helix-coiled-coil-helix domain containing 10 (CHCHD10).…”
Section: Introductionmentioning
confidence: 99%